Country Image and the Study Abroad Destination Choice of Students from Mainland China - Ghazarian, Peter G. (Journal of International Students, 2016)
In this study, the author focuses on the issue of country image in destination choice. To examine the relationship between these two variables, the study tests whether mainland Chinese who favor a destination as their ideal first choice for study abroad have a significantly more positive view of that destination’s country image than their compatriots. The findings suggest policymakers and marketers from most destinations may be more successful focusing on factors other than country image in their attempts to attract cross-border students.